Antidiabetic activity of aquilaria malaccensis (agarwood) leaves extracts - Nur Liyana, Zulkifle (2018)
Diabetes mellitus is defines clinically by hyperglycaemia or an abnormal increased glucose uptake. The purpose of this study was to assess the possible inhibitory effects of methanolic and aqueous leaves extract of A. malaccensis against α-glucosidase and α- amylase activities at concentrations ranged from 100 to 1000μg/ml compared with Acarbose, a commercial drug used in the clinical management of diabetes. Acute and sub-chronic toxicity studies were conducted to observe any toxic effects of A. malaccensis leaves extracts by administrating maximum dose of 2g/kg body weight for 14 days and two concentrations of 250mg/kg and 500mg/kg body weight daily for 28 days, respectively. In vivo study was conducted using STZ-induced diabetic rats model to evaluate the effects of administrating 500mg/kg body weight of methanolic and aqueous A. malaccensis leaves extracts on blood glucose level compared with standard drug, Metformin. A. malaccensis methanolic and aqueous leaves extracts exhibited potent inhibitory effects against α-glucosidase activity with IC50 values of 428.92 and 425.09μg/ml, respectively, compared to Acarbose, with IC50 values of 402.06μg/ml. Similarly, methanolic and aqueous A. malaccensis extracts showed dose dependant inhibitory effects against α-amylase activity with IC50 values of 752.98 and 771.53μg/ml, respectively compared with Acarbose, with IC50 value of 584.93μg/ml. Acute toxicity study of A. malaccensis methanolic and aqueous leaves extracts showed that the extracts did not exhibit any toxic effect in rats and is therefore, likely to be safe for consumption; oral lethal dose (LD50) recorded for all extracts was greater than 2g/kg body weight. Blood serum was analysed for kidney profile and liver function; changes of these values were insignificant and remained within normal range. In vivo study using STZ-induced diabetic rats treated with A. malaccensis methanolic and aqueous leaves extracts at concentration of 500mg/kg body weight for 5 days showed that blood glucose level was significantly decreased by a percentage of 57.08% and 55.48%, respectively, compared with metformin, 68.79%. Assessment of biochemical parameters in diabetic rats treated with both extracts showed that the extracts did not inflict damage to serum protein; the results suggest that these extracts do not cause significant damage to the internal organs, particularly liver and kidney. These results suggest that A. malaccensis methanolic and aqueous extracts can potentially lower the blood glucose level in diabetic individual without inflicting harmful side effects. The extracts can be potentially used as an adjunct in the management of diabetes mellitus as well as development of standardized phytomedicine for diabetes mellitus.